The Contribution of Subunits of Thyroid Stimulating Hormone to the Binding and Biological Activity of Thyrotropin - Wolff, J. (1974)
The binding of bovine TSH (thyroid stimulating hormone), LH (luteinizing hormone), and their subunits to the TSH receptor of beef thyroid membranes was compared to stimulation by these agents of adenylate cyclase [ATP pyrophosphate-lyase(cyelizing), EC 4.6.1.1] in the same membranes, glucose oxidation in dog thyroid slices, and the secretory process in mouse thyroids in vitro (colloid droplet formation) and in vivo (hormone release). The β-subunits of TSH and LH can bind to the TSH receptor and can activate thyroid function in vitro. In contrast, the α-subunit of TSH binds negligibly to the TSH receptor and has very low potency for stimulation of thyroid function (except for colloid droplet formation). Neither binding nor the biological activity of the β-subunits can be accounted for by TSH contamination, whereas this cannot be ruled out for α-TSH. LH binds to the TSH receptor even better than the β-subunit of TSH but the increased binding does not result in a corresponding activation of thyroid function. Neither α- nor β-TSH alone can induce more than 4-8% of the response to intact TSH in any of the investigated parameters. It is proposed that the β-subunit has within its structure the primary determinants which are necessary to stimulate biological activity, whereas the α-subunit imposes conformational changes on the β-subunit which in intact TSH promote binding and biological activity commensurately but in LH promote only binding.